1998
DOI: 10.1046/j.1365-313x.1998.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the Arabidopsis CPD gene, encoding a steroidogenic cytochrome P450, is negatively controlled by brassinosteroids

Abstract: SummaryThe Arabidopsis CPD gene encodes a cytochrome P450 steroid side-chain hydroxylase (CYP90) that plays an essential role in the biosynthesis of the plant hormone brassinolide. Expression of the CPD gene is confined to cotyledons and leaf primordia in etiolated seedlings and detectable in the adaxial parenchyma of expanding leaves in light-grown plants. Transcription of the CPD gene is not affected by the plant growth factors auxin, ethylene, gibberellin, cytokinin, jasmonic acid and salicylic acid, but is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
166
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 216 publications
(175 citation statements)
references
References 41 publications
7
166
2
Order By: Relevance
“…In transgenic Arabidopsis, BR biosynthesis could be increased by overexpression of DWF4/CYP90B1, one of the ratelimiting enzymes (Choe et al, 2001), and parallel changes in the amounts of CPD:b-glucuronidase and native CPD transcripts revealed that the mRNA level of CPD is controlled primarily at the level of transcription (Mathur et al, 1998). Accordingly, reporter fusions with promoters of BR-biosynthetic genes, such as those of CPD, CYP85A1, and CYP85A2, could be used successfully to determine developmental and temporal expression patterns, as well as active sites of BR synthesis (Mathur et al, 1998;Castle et al, 2005). Whereas the crucial role and relatively high transcription level of CPD make its promoter ideal for in vivo expression assays using LUC reporter, such studies require faithful correspondence between the activities of endogenous CPD and the LUC reporter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In transgenic Arabidopsis, BR biosynthesis could be increased by overexpression of DWF4/CYP90B1, one of the ratelimiting enzymes (Choe et al, 2001), and parallel changes in the amounts of CPD:b-glucuronidase and native CPD transcripts revealed that the mRNA level of CPD is controlled primarily at the level of transcription (Mathur et al, 1998). Accordingly, reporter fusions with promoters of BR-biosynthetic genes, such as those of CPD, CYP85A1, and CYP85A2, could be used successfully to determine developmental and temporal expression patterns, as well as active sites of BR synthesis (Mathur et al, 1998;Castle et al, 2005). Whereas the crucial role and relatively high transcription level of CPD make its promoter ideal for in vivo expression assays using LUC reporter, such studies require faithful correspondence between the activities of endogenous CPD and the LUC reporter.…”
Section: Discussionmentioning
confidence: 99%
“…The CPD:LUC1 reporter construct was generated by cloning the 2968 to 25 segment (relative to the translation start) of the CPD promoter (Mathur et al, 1998) into the T-DNA-based binary vector pPCV812 (Koncz et al, 1994), in which the uidA (b-glucuronidase) part had been replaced by the firefly (Photynus pyralis) LUC-derived LUC1 (Promega). The CYP85A2 promoter (2971 to 25) was cloned in the same vector, as was described by Castle et al (2005).…”
Section: Generation Of Transgenic Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CPD gene is expressed in the cotyledons and young leaves of developing seedlings and is down-regulated by BL (34). Because BL is undetectable in rosettes of bas1-D phyB-4, one would expect higher expression of CPD.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the existence of BRs in vascular cells of pine tree has been reported (Kim et al, 1990), it is still unknown if BRs are biosynthesized in the vascular tissues themselves. Mathur and others indicated that a chimeric CPD promoter-uid gene is strongly expressed in palisade cells, suggesting that a key enzyme for synthesizing BRs is expressed in mesophyll cells (Mathur et al, 1998). Although they did not refer to the expression of the chimeric gene in the vasculature, some pictures appear to show a preferential expression of the gene in vascular networks in leaves.…”
Section: Brs Rapidly Increase Before Entry Into the Final Stagementioning
confidence: 99%